Nelson essentials of pediatrics - Marcdante, Karen J.; Kliegman, Robert (Elsevier Saunders, 2015)
Considered the resource of choice for pediatric residencies, clerkships, and exams, Nelson Essentials of Pediatrics provides comprehensive, yet concise and accessible guidance on normal childhood growth and development, as well as the diagnosis, management, and prevention of common pediatric diseases and disorders.